PENGARUH EXPERIENTIAL MARKETING, SERVICE QUALITY, KUALITAS SISTEM INFORMASI WEBSITE TERHADAP MINAT PEMBELIAN ULANG MELALUI KEPUTUSAN PELANGGAN: INFLUENCE OF EXPERIENTIAL MARKETING, SERVICE QUALITY, QUALITY OF WEBSITE INFORMATION SYSTEMS ON REPURCHASING INTEREST THROUGH CUSTOMER DECISIONS - Azharianto, Tunjung Anggitasari; Derriawan Derriawan; Miranda, Agustinus (Pusat Riset dan Inovasi Nasional, 2022)
The purpose of this research is to analyzed factors that affect repurchase intention of IKEA Indonesia products. The variabels used in this research are experiential marketing, service quality, and website information system quality as independent variables, customer satisfaction as communicator variable, while repurchase intention as dependent variable. The sample consist of 300 IKEA AlamSutera and Sentul City consumers. The data that was used in this research was the primary data and selected by using purposive sampling method. Data was processed using Stuctural Equation Modeling (SEM) with SmartPLS. The result of this research provides that experiential marketing, service quality, website information system quality haveinfluence on by significance to customer satisfaction, then experiential marketing, service quality, customer satisfaction have influence on by significance to repurchase intention. Howeverthere’s no evidence that website information system quality on have influence to repurchase intention.